1989
DOI: 10.3109/00365528909090796
|View full text |Cite
|
Sign up to set email alerts
|

Release of Arachidonic Acid Metabolites during Acute Pancreatitis in Pigs

Abstract: The pancreatic release of arachidonic acid metabolites was studied in a porcine model of acute pancreatitis. In situ isolation of the pancreatic gland enabled selective collection of pancreatic venous blood, pancreatic lymph, and ascites fluid. Three experimental groups were studied: 1) control (n = 9); 2) hemorrhagic pancreatitis induced by injection of 5% bile salt (sodium taurocholate) into the pancreatic duct (n = 10); and 3) edematous pancreatitis induced by injection of free fatty acid (FFA) into the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Recently, it has been proposed that the release of secondary inflammatory mediators including interleukin (IL)‐1α, IL‐6, tumour necrosis factor‐α (TNF‐α) and arachidonic acid metabolites contributes to the induction of the systemic inflammatory response and multiple organ failure (Kingsnorth, 1997; Uhl et al ., 1998; Kingsnorth and O'Reilly, 2006). Accumulating evidence indicates the essential role of prostanoids in the pathogenesis of acute pancreatitis (Van Ooijen et al ., 1988; Vollmar et al ., 1989; Zhou et al ., 1994). Previous studies have demonstrated that cyclooxygenase (COX)‐2 mRNA as well as its serum levels are elevated in the setting of AP, particularly in the early stages of the inflammatory process, when the enzyme acts as a pro‐inflammatory agent (Zabel‐Langhennig et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that the release of secondary inflammatory mediators including interleukin (IL)‐1α, IL‐6, tumour necrosis factor‐α (TNF‐α) and arachidonic acid metabolites contributes to the induction of the systemic inflammatory response and multiple organ failure (Kingsnorth, 1997; Uhl et al ., 1998; Kingsnorth and O'Reilly, 2006). Accumulating evidence indicates the essential role of prostanoids in the pathogenesis of acute pancreatitis (Van Ooijen et al ., 1988; Vollmar et al ., 1989; Zhou et al ., 1994). Previous studies have demonstrated that cyclooxygenase (COX)‐2 mRNA as well as its serum levels are elevated in the setting of AP, particularly in the early stages of the inflammatory process, when the enzyme acts as a pro‐inflammatory agent (Zabel‐Langhennig et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The elastase concentration proved significantly lower in edematous pancreatitis in comparison to necrotizing pancreatitis [84]. Ultimately fatal pancreatitis appears to result in a large part from excessive leukocyte stimulation with release of lysosomal enzymes, leukotrienes, and reactive oxygen metabolites, both in the pancreas and elsewhere [55, 85, 86, 87]. …”
Section: Ischemia/reperfusion Injury Of the Pancreasmentioning
confidence: 99%
“…The activated leukocytes adhere to the venular wall of postischemic tissue [23], and exert deleterious injury to the microvasculature as well as to the parenchymal tissue by the release of potent mediators and toxic substances, such as lysosomal enzymes, arachidonic acid metabolites and reactive oxygen intermediates [74]. These mechanisms of tissue injury are in parallel with those discussed for the pathogenesis of pancreatitis: fatal pancreatitis has been suggested to be the consequence of excessive leukocyte stimulation [75], involving the release and action of lysosomal enzymes [75], prostaglandins and leukotrienes [76,77], and reactive oxygen metabolites [78][79][80][81][82]. Moreover, in the isolated, perfused dog pancreas, Kuroda et al [83] demonstrated that leukocytes (and platelets) damage the pancreas during ischemiareperfusion by increasing the peroxidation of structurally important cell membrane lipids, underlining the pivotal role of leukocyte-dependent oxidant stress in acute pancreatitis.…”
Section: Hypovolemic Shock and Pancreatitismentioning
confidence: 77%